Huge Osteoma of the Frontoethmoidal Sinus with Secondary Brain Abscess - Koyuncu, M.; Belet, U.; Şeşen, T.; Tanyeri, Y.; Şimşek, M. (My University, 2000)
Osteomas of paranasal sinuses are usually asymptomatic. When enlarged, they may cause serious complications. We report a case of huge frontoethmoidal osteoma associated with brain abscess. If an osteoma associated with an intracerebral pathology is detected, it should be remembered that this could have been a complication of the osteoma and a detailed radiological examination should be performed to show the extent of the osteoma and to confirm any defect at the posterior wall of the sinus which may lead intracerebral complications. Such an osteoma should be operated after the abscess was resolved and patient became stable neurologically. Copyright (C) 2000 Elsevier Science Ireland Ltd.
Keywords: Brain Abscess; Osteoma